(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Laparotomy for intra-abdominal haemorrhage due to ectopic pregnancy is a common practice in Gynaecology. But laparotomy due to nongynecological causes may rarely happen in this department. A case report is discussed here where abdomen was opened as a case of ectopic pregnancy but subsequently patient needed relaparotomy and finally diagnosed as an atraumatic splenic rupture. The purpose of this paper is to bring this differential diagnosis to clinician’s minds, so that physician can consider the diagnosis of spontaneous nontraumatic splenic rupture. J Bangladesh Coll Phys Surg 2020; 38(2): 98-100